2022
DOI: 10.1128/jvi.00907-22
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mutation in the Main Protease Cleavage Site of Feline Coronavirus Renders the Virus More Resistant to Main Protease Inhibitors

Abstract: CoVs cause serious human infections, and antiviral drugs are currently approved to treat these infections. The development of protease-targeting therapeutics for CoV infection is hindered by resistance mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
0
12
0
2
Order By: Relevance
“…Potential viral resistance has not only been recognized for paxlovid's M pro -active ingredient nirmatrelvir but also for other late-stage M pro antivirals such as GC376 and boceprevir. In fact, a study by Peng and co-workers investigated the development of resistance in a feline coronavirus (FIPV) under pressure from GC376 and found that a mutation in nsp12 of its main protease rendered the enzyme up to three times less susceptible for the inhibitor [109]. Encouraging data from cell culture studies hint that GC376 performs efficiently against M pro 's from SARS-CoV-2 and various seasonal coronaviruses (NL63, 229E, and OC43), suggesting beneficial inhibition promiscuity of this drug that can be used as a basis for future structure development and antiviral testing [110].…”
Section: Inhibitors In Action-drug Performance In the Clinicmentioning
confidence: 99%
“…Potential viral resistance has not only been recognized for paxlovid's M pro -active ingredient nirmatrelvir but also for other late-stage M pro antivirals such as GC376 and boceprevir. In fact, a study by Peng and co-workers investigated the development of resistance in a feline coronavirus (FIPV) under pressure from GC376 and found that a mutation in nsp12 of its main protease rendered the enzyme up to three times less susceptible for the inhibitor [109]. Encouraging data from cell culture studies hint that GC376 performs efficiently against M pro 's from SARS-CoV-2 and various seasonal coronaviruses (NL63, 229E, and OC43), suggesting beneficial inhibition promiscuity of this drug that can be used as a basis for future structure development and antiviral testing [110].…”
Section: Inhibitors In Action-drug Performance In the Clinicmentioning
confidence: 99%
“…[176] RdRp and M PRO represent ideal antiviral targets since both proteases are critical for viral replication. [175,176] Although the efficiency and the efficacy of CNTs as an antiviral COVID-19 treatment are still unclear, [177] theoretical and computational results have been promising for the interaction of CNTs and the SARS-CoV-2 RdRP and M PRO proteases. [36,54,55,174] Molecular dynamic and molecule docking studies by Skariyachan et al [55] proved that CNTs were effective in multiple binding with targets of the SARS-CoV-2 virus, including the papain-like protease.…”
Section: Applications Of Cnts In the Treatment Of Covid-19mentioning
confidence: 99%
“…The main protease (M PRO ), also a 3C-like protease, plays a vital role in RNA virus replication and transcription. [176] RdRp and M PRO represent ideal antiviral targets since both proteases are critical for viral replication. [175,176] Although the efficiency and the efficacy of CNTs as an antiviral COVID-19 treatment are still unclear, [177] theoretical and computational results have been promising for the interaction of CNTs and the SARS-CoV-2 RdRP and M PRO proteases.…”
Section: Applications Of Cnts In the Treatment Of Covid-19mentioning
confidence: 99%
“…Auch eine in-vitro-Studie (Kultivierung von Virus in Zellkulturen in Anwesenheit des Medikaments) zeigte, dass FCoV in der Lage ist, in Anwesenheit von GC376 zu mutieren und eine Resistenz gegen GC376 zu entwickeln. GC376 ist dann unwirksam gegen diese resistenten Mutanten [ 70 ] . Dies beweist, dass ein restriktiver Einsatz dieser potenten antiviralen Medikamente wichtig ist.…”
Section: Gc376unclassified